COGNITIVE AND EDUCATIONAL IMPORTANCE OF THE PRINCIPLES IN GUIDING BY AMIR TEMUR - Rzaeva, J.K. (SCIENCE and SOCIETY, 2019)
The article is devoted to the description of the principles of governing by which the famous state leader Amir Timur was quided in his life. They were given in his book “Timuri-Tuzuki” that was translated into many languages. These principles remain valuable today, and they play a great role in the education of young generation.
Keywords: a ruler; rich historical heritage; military affairs; the book “Temuri-Tuzuki"; principles in quiding; cognitive importance; education of the young generation